Penentuan Waktu Baku dengan Metode Stopwatch Time Study pada Proses Produksi Keripik Singkong Tawar di PT. XYZ - Tresida, Mutiara Putri; Nugroho, Dony Satriyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is a manufacturing industry in the food processing sector that focuses on the production of unsalted cassava chips. Currently, the company is unaware of the standard processing time for producing cassava chips, which impacts delivery schedules, sometimes causing delays due to the high volume of orders received. This study aims to determine the standard time required in the production process of unsalted cassava chips. The research was conducted using the Stopwatch Time Study method, as direct observations were made until sufficient data was collected using a stopwatch and observation sheets. The production process time was measured 10 times. The results showed that the time required for workers to produce unsalted cassava chips is 2181.408 seconds.